The Multifaceted Role of the Lysosomal Protease Cathepsins in Kidney Disease - Cocchiaro, Pasquale; De Pasquale, Valeria; Della Morte, Rossella; Tafuri, Simona; Avallone, Luigi; Pizard, Anne; Moles, Anna; Pavone, Luigi Michele (Frontiers in Cell and Developmental Biology, 2017)
Kidney disease is worldwide the 12th leading cause of death affecting 8-16% of the entire population. Kidney disease encompasses acute (short-lasting episode) and chronic (developing over years) pathologies both leading to renal failure. Since specific treatments for acute or chronic kidney disease are limited, more than 2 million people a year require dialysis or kidney transplantation. Several recent evidences identified lysosomal proteases cathepsins as key players in kidney pathophysiology. Cathepsins, originally found in the lysosomes, exert important functions also in the cytosol and nucleus of cells as well as in the extracellular space, thus participating in a wide range of physiological and pathological processes. Based on their catalytic active site residue, the 15 human cathepsins identified up to now are classified in three different families: serine (cathepsins A and G), aspartate (cathepsins D and E), or cysteine (cathepsins B, C, F, H, K, L, O, S, V, X, and W) proteases. Specifically in the kidney, cathepsins B, D, L and S have been shown to regulate extracellular matrix homeostasis, autophagy, apoptosis, glomerular permeability, endothelial function, and inflammation. Dysregulation of their expression/activity has been associated to the onset and progression of kidney disease. This review summarizes most of the recent findings that highlight the critical role of cathepsins in kidney disease development and progression. A better understanding of the signaling pathways governed by cathepsins in kidney physiopathology may yield novel selective biomarkers or therapeutic targets for developing specific treatments against kidney disease.